Peran Bimbingan dan Konseling Islam dalam Pembentukan Akhlakul Karimah Peserta Didik - Armayani, Ely; Daulay, Nurussakinah (Kamaya: Jurnal Ilmu Agama, 2025)
The number of students experiencing mental pressure due to the burden of memorization, adaptation to the pesantren environment, and limited interaction with family has become a serious concern. These conditions lead to symptoms of stress, anxiety, irritability, and a lack of self-confidence. Therefore, an effective approach is needed to help students overcome these problems. This approach can be supported through Islamic counseling using the dzikir technique, which is closely related to pesantren education. This background encouraged the researcher to conduct a study with the aim of describing the role of Islamic guidance and counseling through the dzikir technique in strengthening the mental resilience of students in one of the Islamic boarding schools in Medan City. This research employed a qualitative method with a phenomenological approach. The data sources consisted of five female students and one counseling teacher. Data collection techniques included in-depth interviews, observation, and documentation. Data analysis was carried out using thematic analysis. The findings of the study indicate that counseling services combined with regular dzikir practices had a positive impact on students’ mental conditions. Students who were previously withdrawn, anxious, and often cried became calmer, more patient, and better able to control their emotions. Dzikir served as a medium for achieving inner peace and closeness to Allah SWT. Moreover, collective dzikir activities also strengthened social bonds among students and fostered strong solidarity. The counseling teacher played a central role in guiding, motivating, and providing a spiritual approach to the students. In conclusion, the dzikir technique in Islamic guidance and counseling services was effective in building mental resilience, nurturing the spirit of worship, and shaping students’ character to be spiritually and emotionally strong. Therefore, further research is needed to develop and expand the use of the dzikir technique in Islamic guidance and counseling services.